Hoken: a transformation guided by the identities of Varberg - Schultz, Alida; Wik, Tove (My University, 2022)
When a place is facing transformation, a balancing act arises between preserving and renewing. What might be seen as a valuation of physical objects to be either kept or removed, is also a selection of memories to bring into the future. As architects, we have a responsibility to understand the place and not let norms guide these decisions at the expense of local, everyday qualities experienced by the users. An understanding of the unique atmosphere is crucial to consider in a place’s development, as it is closely associated with the feeling of belonging and identification. The thesis focuses on a part of a development area in Varberg that is currently in transition. The harbour that shaped the town, will be replaced by a new urban-influenced city district, Västerport. Hoken, a pier located at the interface between the old Varberg and the upcoming neighbourhood, is included in the transition but its future is still uncertain. This is the starting point of the thesis. The aim is to explore methods for capturing and conveying place identity, with collages as a narrative design tool, and to use the guiding narrative as the main driver for a transformation proposal. The thesis is mainly driven by a research-by-design method, supported by literature studies to frame the theoretical approach. During the process we aim to understand the site with a phenomenological mindset, which puts emphasis on capturing not only physical characteristics, but also making intangible aspects visible. By drawing in layers, physical objects can be supplemented with activity and strengthened by an emphasised feeling. One by one, the collages create scenes. Together, they tell the story of Varberg. The result of the thesis can be divided into two parts, the architectural proposal and the methodology behind it. The captured place identity guides the transformation process, in order to protect the attachment between the people and the place. The outcome is a transformation proposal for Hoken, into a new public space, that allows for Varbergs unique atmosphere to flourish despite times of urban renewal.
Keywords: Transformation, Place identity, Tangible and intangible heritage, Narrative thinking, Collage